Are you ready for retirement? The influence of values on membership in voluntary organizations in midlife and old age - Sánchez-García, Julia; Vega-Tinoco, Andrea; Gil-Lacruz, Ana I.; Mira-Tamayo, Diana C.; Moya, Miguel; Gil-Lacruz, Marta (Frontiers in Psychology, 2022)
Membership in voluntary organizations is associated with individual and social benefits. Due to the negative consequences of the global pandemic on older people, and the governmental challenges posed by population aging, voluntary membership is of great importance to society. To effectively promote volunteering among older people, it is necessary to understand the determinants of voluntary membership. This study analyses the influence of individual values – secular/traditional and survival/self-expression - on voluntary membership among European adults. Specifically, it examines which values orient two age groups (middle age: 50-64 and old age: 65-79), as well as men and women towards a certain type of association (Social Awareness; Professional and Political; Education and Leisure; Religion). Individual-level variables from the Integrated Values Survey (2005/09, 2010/14, and 2017/20) are used along with national-level variables (Gini Index and Gross Domestic Product Per Capita) from the World Bank and Eurostat. The results indicate that traditional and self-expression values promote membership in voluntary organizations in general more than secular and survival values. However, there are differences according to the type of organization. Furthermore, values are found to moderate the effect of age and gender on voluntary membership.